风力发电齿轮箱设计制造技术的发展与展望 - 刘忠明; 段守敏; 王长路 (Jixie chuandong)
Current status and development trend of global wind power are summarized. Some key technologies of design and manufacture of gearboxes for MW wind turbines are expatiated. Main content of ANSI 6006-A03 is described. Actuality, problems and perspective on gearboxes for wind turbines in China are analyzed.